Bridging a Gap: Indonesian English Teachers’ Views on ELF and Its Role in Workplace Communication - Panggabean, Hanna Maria; Samosir, Sahat Maringan (Prodi Sastra Indonesia, FKIP Universitas Jambi, 2025)
This study explores Indonesian English teachers' perspectives on English as a Lingua Franca (ELF) and its importance in workplace communication. Using grounded theory and narrative inquiry, the research investigates the experiences of four vocational English teachers to identify challenges, strategies, and suggestions for curriculum reform. The findings revealed that teachers frequently face psychological and linguistic obstacles, such as limited vocabulary and cultural differences, which hindered effective ELF communication. To address these issues, teachers employed pragmatic strategies and cultural adaptation techniques to facilitate workplace interactions. The study highlights the need to shift from traditional grammar-focused instruction toward ELF-informed methodologies that emphasize comprehensibility, intercultural competence, and practical communication skills. This approach aims to better prepare vocational Indonesian students for the complexities of global workplace environments. Overall, the research suggests for an inclusive and flexible English education system that strengthen intercultural understanding and communicative proficiency, essential for successful international collaboration and cross-cultural communication.